Growth of Puntazzo puntazzo in cages in Selonda bay, Corinthos, Greece - Gatland P. (Marine aquaculture finfish species diversification, 1995)
In February 1992, 32,822 Puntazzo puntazzo fry of 0.55g mean weight were stocked initially into a cage in Selonda Bay, Corinthos, Greece. This batch reached a mean weight of 377 grams in 29 months to produce 8753.5 tonnes with a mortality of 17.8 per cent and FCR of 1:3. In February 1993 a further two batcher of 65, 854 and 81.620 Puntazzo fry produced from the Selonda hatchery were stocked at 1.6g and 1 gram mean weight respectively, into cages in Selonda Bay and in April 1994 a further batch of 34,580 was stocked at 4,5 grams. The growth, mortality, FCR, pathology and husbandry of this commercial pilot production of Puntazzo puntazzo is described.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1995/06/14-17, Nicosia (Cyprus)